Effect of Birth Balls on Reducing Labor Pain During First Stage of Active Phase in Primigravida Maternity - Dahlan, Febry Mutiariami; Suciawati, Anni; Sri, Fadila (International Journal of Midwifery and Health Sciences, 2023)
Background: Pain in labor is a manifestation of shortening contractions of the uterine muscles. Data on maternity of primigravida in Indonesia, as many as 54% felt severe pain, as many as 46% experienced moderate pain and mild pain. It is important for health services to always use non-pharmacological measures to relieve labor pain. Purpose: The purpose of this study was to assess effect of use of birth balls on reducing of labor pain during first stage of active phase in primigravida maternity at the Public Health Center of Sawah Besar Subdistric. Methods: This research used Pre-Experimental Design with one group pretest – posttest design type. The samples used the minimum requirement of experimental samples, namely 30 maternity mothers. Instrument in this research used questionnaires. Bivariate analysis used paired t-test. Results: After analysis, the average value for reduction of pain before used birth ball was 84.33. The average reduction of pain after used birth ball was 65.67. There is an effect of use of birthball on reducing of labor pain during first stage of active phase in primigravida maternity at the Public Health Center Sawah Besar Subdistric in 2019 (p value 0.000). Conclusion: The conclusion was that there was an effect of the use of birthball on reducing of labor pain during first stage of active phase in primigravida maternity. The results suggest Using birth balls can be used as an alternative to non-pharmacological therapy in management of labor pain during the active phase. This effort can be applied in practice and as material for further research.